Das Umlageverfahren: Idee und Wirklichkeit - Fritz Helmedag (Wirtschaftsdienst, 2024)
– The formal relationships between the contribution rate of workers and the pension level are modelled in the pay-as-you-go system. The average pensioner has paid contributions over 36 years and currently receives EUR 1,246.67 as a monthly pension. The 'standard pensioner' contributed over 45 years and receives a 'standard pension' of EUR 1,692. The real pension level is 42.6% and thus falls short of the 48% target level. In the pay-as-you-go system, the monthly pension would only amount to EUR 1,203.66. Higher contributions reduce average wages relatively less than they increase the pension benefits. A redistribution within the pool of insured people should compensate for the shorter payment periods of below-average pensions.
Keywords: H55; I38; J14; 330; Gesetzliche Rentenversicherung; Deutschland; Gesetzliche Rentenversicherung; Deutschland